Two Cases of 188Re Microspheres for Inoperable Hepatocellular Carcinoma. (February 2019) - Shukla, Jaya; Kalra, Naveen; Kumar, Rajender; Bhusari, Priya; Chhabra, Anupriya; Parmar, Madan; Vatsa, Rakhee; Singh, Harmandeep; Duseja, Ajay; Mittal, B. R.
Abstract : Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal malignancies. Often, patients present with inoperable and advanced disease. Selective internal radionuclide therapy offers prolonged survival and improved quality of life by delivering high radiation dose to the tumor with minimal complications. We report 2 inoperable cases of HCC treated with therapeutic dose of indigenously developed 188 Re microspheres delivered to the hepatic lesions by transarterial catheterization. Follow-up CT revealed necrosis within the lesion, suggesting response to selective internal radionuclide therapy. 188 Re microspheres may be a potential treatment option for inoperable HCC with or without portal vein thrombosis.